Chronic kidney disease (CKD): The silent epidemic. The importance of early detection and treatment on the prevention of CKD - (:unkn) unknown (My University, 2005)
The incidence and prevalence of end-stage renal disease (ESRD) is increasing worldwide. Despite the absence of precise epidemiological data, it is known that there are a great many patients in the conservative phase of chronic kidney disease (CKD). In this context, any medical intervention that may prevent the progression of CKD towards ESRD is extremely important. Improving the patients' cardiovascular status is also a major objective in the management of this population, as cardiovascular disease is the leading cause of morbidity and mortality for dialysis patients.
Keywords: Cardiovascular Disease; Chronic Kidney Disease; Epidemiology; Prevention